Challenges to Physicians: Hospital Immunity and Sham Peer Review - Poston Robert; Gharagozloo Farid; W.G. Gruessner Rainer (Journal of Human Psychology, 2023)
An opinion essay examines hospital immunity doctrines and alleged sham peer review, outlining legal context, patient‑safety implications, and avenues for due process.